A (wo)men’s revolution?: Small feet, large hands and visions of womanhood in China’s long twentieth century - Mittler, Barbara (Routledge handbook of revolutionary China, 2019)
Different times and different regimes propagate different images of the ideal woman and her body. In China’s long twentieth century, the emblematic features of an ideal woman have wavered between one extreme of the woman with small (bound) feet, beautifully delicate, or, as one would say at another time, sickly and fragile, and that of the woman with large hands and muscular arms and legs, healthy and strong, or, as one would say from another perspective, masculine and plump. This chapter traces evidence for these two idealized visual regimes and their transcultural engendering and studies the different foreign and Chinese ideologies behind their making and their propagation. In presenting visual itineraries of suggestive and didactic imagery created throughout the twentieth century in China, the chapter will argue that in spite or because of all the many (wo)men’s revolutions that China has seen, even until today, the two extremes, small feet and large hands, play a significant role in the framing and reframing of female bodies and body ideals.
Gesehen am 02.11.2023